The Use of Podcast as a Creative Learning Resource in Social Studies - Nur’aini, Fatwa; Supriatna, Nana; Ratmaningsih, Neiny (Jurnal Paedagogy, 2023)
This study aims to describe the use of podcast media as a learning resource in social studies learning and identify obstacles encountered. The method used in this study was the phenomenological method. The study subjects were students of SMP Kesatrian 1 Semarang City, which totaled 26 students, and teachers who taught social studies subjects. Interviews, observation, and documentation were done to collect the data. Interviews were used to obtain data using question and answer with informants. Data analysis was carried out in a study to draw conclusions from all the data that had been obtained. Researchers used data analysis techniques consisting of (1) Data collection, (2) Data Reduction, (3) Data presentation, and (4) Conclusion retrieval or verification. The research results were podcast media as an innovative and creative learning resource to be used in social studies learning in and outside the classroom. The use of podcast media as a learning resource is divided into three stages: the three stages’ planning, implementation, and evaluation stages are carried out systematically. Based on this research, 76.92% of students understood learning materials with podcast media as a learning resource. In addition, there were 23.08% of students had difficulty using podcast media. It was due to several obstacles, both internally and externally. The internal obstacle was the need for memory capacity to access the Spotify application on the student’s mobile phone. External obstacles existed due to learning distractions from the family environment if learning was carried out at home.